BUDIDAYA HIJAUAN MAKANAN TERNAK SISTEM TIGA STRATA DAN PEMBUATAN SILASE KOMPLIT DI KELOMPOK TANI SERIKAT OELIURAI KABUPATEN TTU-NTT - Gerson Frans Bira; Paulus Klau Tahuk; Boanerges Putra Sipayung; Charles Venerius Lisnahan; Agustinus Bria Laka; Ludowika Jessye Jelita Ninu; Carla Krisanti Fios (LP2M Universitas Hasanuddin, 2024)
The production of ruminants in the tropics characterized by dry land is highly dependent on feed with a benchmark of availability depending on nature. There is an imbalance in the availability of feed in the rainy season and dry season so livestock productivity fluctuates with changing seasons. Efforts that can be made to provide feed throughout the season are planting forage for superior adaptive feed (three strata system) and making complete silage. This service activity aims to educate and provide experience to the Serikat Oeliurai farmer group to provide quality and available feed throughout the season through planting forage with a three-strata system and making complete silage. The method used in this activity is counseling in the form of lectures followed by direct practice (demo process) and full participation (participatory action research) from partner groups. The activities carried out are a series of activities starting from counseling on superior adaptive forage, training in making bokashi fertilizer, forage seed nurseries, land processing, and forage planting using a three-strata system, and making complete silage. The forages planted are legumes such as Gliricidia sepium (strata 3), Leucaena leucocephala, Indigofera, and Sesbania grandiflora (strata 2) as well as Pennisetum purpureum cv. Mott and Pennisetum purpuphoides (strata 1) with the core consisting of creeping legumes such as Clitoria ternatea and Centrosema pubescens as well as food crops. The activeness and seriousness of the farmer groups can be seen from the presence and discussion that is built from the beginning to the end of the series of activities as well as the active participation of the partner groups with the help of the students involved. The results of the activity showed that the knowledge of partner groups related to forage, planting forage with a strata system, making organic fertilizers, and making complete silage increased from 35% to 97.56%. Likewise, organic fertilizers and complete silage made together are of high quality which can be seen from the organoleptic (color, texture, and aroma). Monitoring will continue to be carried out by the implementing team until the forage is harvested. — Produksi ternak ruminansia di daerah tropis berciri lahan kering sangat tergantung pada pakan dengan patokan ketersediaan bergantung pada alam. Ada ketimpangan ketersediaan pakan pada musim hujan dan usim kemarau sehingga produktivitas ternak berfluktuatif seiring perubahan musim. Upaya yang dapat dilakukan untuk menyediakan pakan sepanjang musim adalah penanaman hijauan pakan unggul adaptif (sistem tiga strata) dan pembuatan silase komplit. Kegiatan pengabdian ini bertujuan untuk mengedukasi dan memberikan pengalaman kepada kelompok tani Serikat Oeliurai dalam upaya menyediakan pakan berkualitas dan tersedia sepanjang musim lewat penanaman hijauan sistem tiga strata dan pembuatan silase komplit. Metode yang digunakan dalam kegiatan ini adalah penyuluhan dalam bentuk ceramah dan diikuti dengan praktek secara langsung (demo proses) serta partisipasi penuh (participatory action research) dari kelompok mitra. Kegiatan-kegiatan yang dilakukan merupakan rangkaian kegiatan yang dimulai dari penyuluhan tentang hijauan makanan ternak unggul yang adaptif, pelatihan pembuatan pupuk bokashi, persemaian bibit hijauan, pengolahan lahan dan penanaman hijauan menggunakan sistem tiga strata serta pembuatan silase komplit. Hijauan yang ditanam adalah jenis legum seperti gamal (strata 3), lamtoro teramba, indigofera dan turi (strata 2) serta rumput odot dan rumput raja (strata 1) dengan bagian inti terdiri atas legum merambat seperti clitoria dan centrosema serta tanaman pangan. Keaktifan dan keseriusan kelompok tani sangat terlihat dari kehadiran dan diskusi yang terbangun dari awal hingga akhir rangkaian kegiatan serta pastisipasi aktif dari kelompok mitra dengan bantuan mahasiswa yang dilibatkan. Hasil kegiatan menunjukkan bahwa pengetahuan kelompok mitra berkaitan dengan hijauan pakan, penanaman hijaun pakan sistem tiga strata, pembuatan pupuk organik, pembuatan silase komplit meningkat dari 35% menjadi 97,56%. Demikian pula pupuk organik dan silase komplit yang dibuat bersama berkualitas yang terlihat dari organoleptik (warna, tekstur dan aroma). Pemantauan akan terus dilakukan oleh tim pelaksana hingga pemanenan hijauan.